Dynamic equilibrium: influence of environmental constrainsts - Veronica Silva Miyasike; Cibele Regina Secco; Cássia Borges Lima; Lilian Teresa Bucken Gobbi (Universidade Federal de Santa Catarina, 2001)
The aims of this study were: (a) to verify the locomotor strategies used when increased environmental constraints are applied to children; and (b) to relate the locomotor behavior within these conditions with the participants' intrinsic characteristics. Two experiments were designed varying the height (ground and 39 cm in Experiment 1 and 39 cm and 120 cm in Experiment 2) where children (3 to 10 years old in Experiment 1 and 3 to 7 years old in Experiment 2) were walking. In both studies, children presented foot position preference (ﬂ at foot), increased number of steps and decreased step length related as height increased. Participants' intrinsic variables and foot position explained the variability in locomotor behavior. It can be inferred that dynamic equilibrium is an important variable in motor control during locomotor tasks in complex environments. RESUMO Os objetivos do estudo foram: (a) verificar estratégias locomotoras utilizadas quando crescentes restrições ambientais são aplicadas a crianças; e (b) relacionar comportamento motor nestas condições com características intrínsecas dos participantes. Dois experimentos foram delineados variando a altura (solo e 39 cm no experimento 1 e 39 e 120 cm no experimento 2) onde crianças (3 a 10 anos no experimento 1 e 3 a 7 anos no experimento 2) andaram. Em ambos os experimentos, as crianças apresentaram preferência no posicionamento do pé (pé plano), aumento na quantidade de passadas e diminuição no comprimento das passadas com aumento da altura. Variáveis intrínsecas aos participantes e posicionamento do pé explicaram a variabilidade no comportamento locomotor. Pode-se inferir que o equilíbrio dinâmico é uma importante variável no controle motor durante tarefa locomotora em ambiente complexo.